DEVELOPMENT OF MODIFICATION MODELS IN IMPROVING MASTERY OF BASIC TECHNIQUES THROWING DISCS - Haryono (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2017)
The purpose of this research is to improve the mastery of the basic technique of throwing disc through the development of modification model for second grade students of SMA. In addition, this research was conducted to get more information about the development of modification model. And to know the effectiveness, efficiency and attractiveness of the modified model development in improving mastery of the basic technique of throwing discs for senior high school students. The design of this research is 45 students of class III SMA N 2 Palangka Raya. The instrument used in this research is pretest and non test to collect data To know the success or failure of the action that has been executed based on the action plan specified, then the criterion used is sourced from the purpose or the mission of doing the action with the criteria used as the benchmark of the success of the action Intended is the achievement of learning mastery of at least 85% of students above the value of ? 65.0%. In this study consists of two cycles, on the implementation of cycle 1 realized through the development of modification model obtained the results of the study concluded that the model developed on learning mastery of basic techniques throwing discs in the first cycle of 66.7 including the category less. The second cycle performed by the results of reflection cycle 1 provides motivation to the students according to the average result plan 81.1%. Including good category. Overall the results of this study is considered successful completion of 91.11% so that the hypothesis of an increase in mastery of basic techniques throwing disc students through the development of the modification model is accepted. With the higher interpretation of the development of modification model will be higher also the level of mastery of basic techniques throwing disc students class III SMA N 2 Palangka Raya